2010
DOI: 10.5271/sjweh.3081
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancy between objective and subjective measures of job stress and sickness absence

Abstract: Rehkopf DH, Kuper H, Marmot MG. Discrepancy between objective and subjective measures of job stress and sickness absence. Scand J Work Environ Health. 2010;36(6):449-457.Objectives The aim of this study was to examine the association of the discrepancy between externally and self-assessed measures of work environment with long-and short-term sickness absence.Methods The study population included 6997 middle-aged men and women from the Whitehall II cohort, whose work characteristics were examined at baseline (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 26 publications
1
14
0
1
Order By: Relevance
“…This is in contrast with some previous studies stating an association of high demands with absenteeism 31,32) . However, the association of high demands with lower sickness absence figures was also demonstrated in a sample from the Whitehall II cohort 33) . A possible explanation is that selection of ambitious workers occurred in this predominantly white-collar sample.…”
Section: Discussionmentioning
confidence: 85%
“…This is in contrast with some previous studies stating an association of high demands with absenteeism 31,32) . However, the association of high demands with lower sickness absence figures was also demonstrated in a sample from the Whitehall II cohort 33) . A possible explanation is that selection of ambitious workers occurred in this predominantly white-collar sample.…”
Section: Discussionmentioning
confidence: 85%
“…Further, an objective change in workplace conditions – downsizing – has been reported to both increase [34] and decrease [35] sickness absence, although these responses may be subject to type of employment contract and local social conditions. Rehkopf [36] in a further analysis of Whitehall II data suggested that whilst sickness absence was differentially predicted by subjective and objective measures of job demands, no such difference was observed for decision latitude.…”
Section: Introductionmentioning
confidence: 95%
“…Time pressure may be harmful to employees’ health and well-being, although the evidence on the relationship between time pressure and absenteeism is still inconclusive 5 6. Psychosocial time pressures, such as tight deadlines, perceived time pressure, or a time famine, may be more important for health than hours spent on the job 7.…”
Section: Introductionmentioning
confidence: 99%